2019
DOI: 10.1186/s12882-019-1645-y
|View full text |Cite
|
Sign up to set email alerts
|

Burden of acute kidney injury and 90-day mortality in critically ill patients

Abstract: BackgroundMortality rates associated with acute kidney injury (AKI) vary among critically ill patients. Outcomes are often not corrected for severity or duration of AKI. Our objective was to analyse whether a new variable, AKI burden, would outperform 1) presence of AKI, 2) highest AKI stage, or 3) AKI duration in predicting 90-day mortality.MethodsKidney Diseases: Improving Global Outcomes (KDIGO) criteria using creatinine, urine output and renal replacement therapy were used to diagnose AKI. AKI burden was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…Patients in this cluster also suffered from more severe AKI than other clusters. AKI and the associated electrolyte imbalances and acidbase disorders may have contributed to the observed increased mortality risk [29][30][31][32]. In addition, they were more likely to have comorbidities, including diabetes mellitus and cirrhosis, which have been shown in prior studies to portend a worse prognosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Patients in this cluster also suffered from more severe AKI than other clusters. AKI and the associated electrolyte imbalances and acidbase disorders may have contributed to the observed increased mortality risk [29][30][31][32]. In addition, they were more likely to have comorbidities, including diabetes mellitus and cirrhosis, which have been shown in prior studies to portend a worse prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…Although clusters #2 and #3 were older and had higher comorbidities than those in cluster #4, patients in clusters #4 carried higher in-hospital and one-year mortality risks. This is likely due to the significant impacts of AKI severity, infectious disease, and hyponatremia on poor outcomes [32,33]. The findings of our study suggest that the use of the ML approach may help identify potential new pathophysiological pathways leading to CA-AKI.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we confirmed the association of AKI and ICU treatment in AML patients as already described by others [ 8 , 19 ]. Sepsis-associated inflammatory response with a potential disruption of renal perfusion as a consequence is known to be a common risk factor for AKI ( https://kdigo.org/wp-content/uploads/2016/10/KDIGO-2012-AKI-Guideline-English.pdf ) [ 6 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, TRM remains at a level of 8-15% during induction chemotherapy [3,4]. AKI is one of the most important organ failures associated with increased mortality and need for ICU treatment in hospitalized patients [6,17]. To the best of our knowledge, the last investigation on the role of AKI in adult patients with AML undergoing intensive induction therapy was published in 2010, while the most recent investigation focused on pediatric AML populations [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation